Two new species of the genus Sorolopha Lower (Lepidoptera: Tortricidae) from northern Thailand - Patibhakyothin, Nathaphan; Pinkaew, Nantasak; Sukprakob, Nutchaya (Zootaxa, 2015)
Two new species of Sorolopha Lower (i.e., S. suthepensis, n. sp., and S. undula, n. sp.) are described and illustrated from male specimens collected in agricultural areas and natural forest in Doi Suthep-Pui National Park, Chiang Mai Province, Thailand.